Acyl Group Migration in Pyranosides as Studied by Experimental and Computational Methods. Issue 34 (11th May 2022) - Lassfolk, Robert; Pedrón, Manuel; Tejero, Tomás; Merino, Pedro; Wärnå, Johan; Leino, Reko
Abstract: Acyl group migration affects the synthesis, isolation, manipulation and purification of all acylated organic compounds containing free hydroxyl groups, in particular carbohydrates. While several isolated studies on the migration phenomenon in different buffers have been reported, comprehensive insights into the overall migration process in different monosaccharides under similar conditions have been lacking. Here, we have studied the acyl migration in different monosaccharides using five different acyl groups by a combination of experimental, kinetic and theoretical tools. The results show that the anomeric configuration in the monosaccharide has a major influence on the migration rate, together with the relative configurations of the other hydroxyl groups and the nature of the migrating acyl group. Full mechanistic model, based on computations, demonstrates that the acyl migration proceeds through an anionic stepwise mechanism with linear dependence on the [OH − ] and the pKa of the hydroxyl group toward which the acyl group is migrating. Abstract : A comprehensive experimental and computational study on acyl migration in different monosaccharides with five different acyl groups, under similar conditions, provides conclusive evidence for the anionic, stepwise migration mechanism, which depends on the concentration of the hydroxyl anion and pKa of the receiving hydroxyl group, together with the anomeric and relative configurations of the carbohydrate in question.